RETRACTED: Formation of environmental literacy through the study of green chemistry - Seisova Assel; Khamzina Sholpan; Khassenova Maral; Mukanova Roza (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001